End-of-life and bereavement support to families in cancer care: a cross-sectional survey with bereaved family members - Qëndresa Thaqi; Marco Riguzzi; David Blum; Simon Peng-Keller; Anja Lorch; Rahel Naef (BMC, 2024)
Abstract Background Losing a close other to cancer is an incisive experience that occurs after a long course of illness and intense family caregiving. Despite an evident need for family engagement and support and guidance on this, patients and family members may not receive the attention and support they need when a family unit is experiencing a disruption by death. A clear understanding of the quality of care that is currently provided and its ability to address family needs is necessary to improve end-of-life and bereavement support to families affected by cancer. The purpose of this study is to investigate the quality of support of end-of-life and bereavement care to families, their (un)met needs, grief experiences, and self-perceived health outcomes. Methods A multi-center, cross-sectional observational survey study with family members (n = 35) whose close other died of cancer in a health institution or their own home in German-speaking Switzerland. Results Bereaved family members were mostly satisfied with end-of-life care. Information on the grief process and services, and acknowledgment of their grief was experienced as helpful. Most coped with their grief drawing on family resources and exhibited resilience, but they reported unmet needs in relation to family togetherness and caregiving. Conclusion This study with a small number of family members indicates that support provided to families across settings and illness trajectories is perceived as helpful, with specific needs related to family support. The findings suggest that improvements should focus on ensuring care that addresses the family as a unit and enables togetherness, mutual reflection, meaningful relationships, preparedness for death, resilience, and benefit-finding. Protocol registration https://osf.io/j4kfh .